Analisis Anggaran Biaya Produksi Sebagai Alat Perencanaan dan Pengendalian Biaya pada PTPN IV Regional III Unit Kebun PKS Sei Intan (Rokan Hulu) Tahun 2024 dan 2025 - Pretty Nur A’yuni Laoli; Heny Tiastuti Kurnia Ningsih; Shofwan Andri (Universitas Islam Islam Sumatera Utara, 2026)
This study aims to analyze the preparation process of the Production Cost Work Plan and Budget (RKAP) and compare it with the realization of production costs at PT Perkebunan Nusantara IV Regional III, Sei Intan Palm Oil Mill Unit, during 2024 and 2025. This research employed a qualitative descriptive method using primary data collected through observation, interviews, and documentation. The study focuses on examining the extent to which the production cost budget functions as a planning and control instrument in supporting the effectiveness of the company's operational management. The findings indicate that the RKAP preparation process applies a combination of bottom-up and top-down planning approaches, enabling the company to accommodate operational needs while aligning with management policies. Furthermore, the production cost budget has been effectively implemented as a planning and control tool. Although several variances were identified between the budgeted and actual production costs, these deviations remained within acceptable limits and could be justified in accordance with the company's established policies and operational standards.